I Would Speak Up to Live Up to Your Trust: The Role of Psychological Safety and Regulatory Focus - Song, Yu; Peng, Peng; Yu, Guangtao (Frontiers in Psychology, 2020)
Voicing upward refers to employee efforts to improve organizational functioning by making suggestions or expressing opinions and concerns. While extant studies have investigated how supervisors’ behaviors or attitudes influence employee voice behaviors, researchers have paid little attention to the effects of employee perceptions on voice. Based on the theory of planned behavior, we developed and tested the effects of feeling trusted by supervisors and two dimensions of voice (promotive and prohibitive), focusing on the mediation role of psychological safety and the interaction effect of psychological safety and regulatory focus on voice. Using a sample of 244 participants and three waves of longitudinal data, we investigated whether feeling trusted would lead to both promotive and prohibitive voice through psychological safety. We also extensively examined the moderation effect of regulatory focus on psychological safety and the contingency dimension of voice. We found that promotion focus strengthens the positive relationship between psychological safety and voice (both promotive and prohibitive voice), whereas prevention focus strengthens the positive relationship between psychological safety and prohibitive voice. This paper concludes with a discussion of the theoretical and practical implications of these findings.